IMPLEMENTASI METODE KOOPERATIF MODEL GROUP INVESTIGATION DALAM MENINGKATKAN BELAJAR MATEMATIKA SISWA SDN 2 SONI DAMPAL SELATAN - Ni Komang Rollicking (Scolae: Journal of Pedagogy, 2019)
Cooperative learning is a teaching that involves students to work in groups to set common goals. Cooperative learning is a learning strategy by placing students in small groups that have different abilities. Cooperative learning methods focus on class activities in students by grouping students to work together in the learning process. The purpose of this study is to improve student learning through the Group Investigation model and to find out the effect of the Group Investigation cooperative learning method on student motivation. The method used in this research is action research as many as three rounds. Each round consists of four stages: design, activity and observation, reflection, and refinement. The target of this research is the fourth grade students of SDN 2 Soni South Dampal. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. The results of research analysts show that student achievement has increased from cycle I to cycle III namely, cycle I (65.00%), cycle II (75.00%), cycle III (85.00%). The conclusion of this study is the cooperative method of the Group Investigation model can positively influence the learning motivation of Students IV SDN 2 Soni Dampal Selatan and this learning model can be used as an alternative to learning mathematics.